Influence of reference trees on N2fixation estimates in Leucaena leucocephala and Acacia albicia using 15N_ labelling techniques+A51 - Sanginga, N.; Danso, S.K.A.; Zapata, F.; Bowen, G.D. (Springer, 1990)
We examined the suitability of four reference crops, i.e., two non-fixing trees,Cassia siamea andEucalyptus grandis, and two uninoculated fixing trees,Leucaena leucocephala andAcacia albida, for measuring fixed N2 fixed in inoculatedL. leucocephala andA. albida grown for 36 weeks in pots. The15N isotope-dilution (involving the addition of equal amounts of labelled N fertilizer to the non-fixing and the fixing plants) and theA-value (with different amounts of labelled N fertilizer added to the fixing and the non-fixing crops) methods were used. The isotope dilution approach gave several large negative estimates of fixed N2 inA. albida. Positive and similar values of fixed N2 were measured in all four reference crops using theA-value approach. ForL. leucocephala the isotope-dilution approach gave different estimates of fixed N2, with the different reference crops; the uninoculated N2-fixing crops indicated significantly less fixed N2 than the non-fixing reference crops. Similar values for N2 fixed inL. leucocephala were obtained using the two non-fixing trees, either by the isotope-dilution or theA-value method. On average,A. albida derived about twice as much N from fertilizer asL. leucocephala. In both species, the atom %15N excess declined by about 50% in successive harvests.